The Struggle over Slavery in the Maritime Colonies - Whitfield, Harvey (Acadiensis, 2012)
This article closely examines the ways in which masters and slaves struggled to define slavery in the Maritimes. Building on the work of previous scholars, special attention is given to the role that African-descended peoples played in ending slavery with the help of local abolitionists and sympathetic judges. The end of slavery brought to the forefront a new and more virulent form of racism that circumscribed opportunities for free black communities in the region.